A new pricing model of China's parallel rail lines under the diversified property rights - Shaoni Zhou; Qiusheng Zhang; Xiaowei Wu (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The purpose of this paper is to study on the pricing of China railway company under the background of diversified property rights, especially the pricing of the parallel line system that belong to different owners. Design/methodology/approach: Through theoretical analysis of the main influential factors of railway pricing, this paper designs a basic quotation system for the parallel railway lines. Findings: The transaction price of parallel line consists of two parts, which are fixed railway network price and variable network using price. Practical implications: Through the reasonable designing of fixed network price and variable network using price, it can not only lead to high profitability and low government subsidy, but also can ensure remaining more railway network resources and fulfill the social responsibilities. Originality/value: The conclusions of this study will lay the foundation for the harmonious development of Chinese railway network under the diversified property rights.
Keywords: 650; Diversified Property Rights; Parallel Rail Lines; Pricing Model